Catalytic activity of violet phosphorus-based nanosystems and the role of metabolites in tumor therapy - Zhang, Hanjie (2024)
Although nanocatalytic medicine has demonstrated its advantages in tumor therapy, the outcomes heavily relie on substrate concentration and the metabolic pathways are still indistinct. We discover that violet phosphorus quantum dots (VPQDs) can catalyze the production of reactive oxygen species (ROS) without requiring external stimuli and the catalytic substrates are confirmed to be oxygen (O2) and hydrogen peroxide (H2O2) through the computational simulation and experiments. Considering the short of O2 and H2O2 at the tumor site, we utilize calcium peroxide (CaO2) to supply catalytic substrates for VPQDs and construct nanoparticles together with them, named VPCaNPs. VPCaNPs can induce oxidative stress in tumor cells, particularly characterized by a significant increase in hydroxyl radicals and superoxide radicals, which cause substantial damage to the structure and function of cells, ultimately leading to cell apoptosis. Intriguingly, O2 provided by CaO2 can degrade VPQDs slowly, and the degradation product, phosphate, as well as CaO2-generated calcium ions, can promote tumor calcification. Antitumor immune activation and less metastasis are also observed in VPCaNPs administrated animals. In conclusion, our study unveils the anti-tumor activity of VPQDs as catalysts for generating cytotoxic ROS and the degradation products can promote tumor calcification, providing a promising strategy for treating tumors.